APPLICATION OF BEHAVIORAL CONTRACT TECHNIQUES TO IMPROVE THE DISCIPLINARY BEHAVIOR OF CLASS VII STUDENTS OF HIDAYATUN NAJAH SMP KALIPURO BANYUWANGI: PENERAPAN TEKNIK BEHAVIORAL CONTRACT UNTUK MENINGKATKAN PERILAKU DISIPLIN SISWA KELAS VII SMP HIDAYATUN NAJAH KALIPURO BANYUWANGI - sri wahyuni; Siti Napisah; Fajar Wahyu Prasetyo (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
Sri Wahyuni, 2020; Application of Behavioral Contract Techniques to Improve Disciplinary Behavior of Class VII Students at Hidayatun Najah Middle School Kalipuro Banyuwangi; 134 pages; Guidance and Counseling Study Program, Faculty of Teacher Training and Education, PGRI Banyuwangi University, Supervisor (1) Siti Na separate, M.Psi, Psychologist. (2) Fajar Wahyu Prasetyo, M.Pd. Contract behavior techniques are one of the behavioral counselling techniques used to remove maladaptive behaviors and form new adaptive behaviours. Contracts are interventions by schools to change student behaviour and monitor using simple agreements. Contract behavior behaviors are chosen because in the contract behavioral techniques individuals are trained to create new behaviours or reduce negative behaviour by giving rewards when the desired behavioure is realized so that such behavioures become consistent. The phenomenon that is encountered in Hidayatun Najah High School is often found students who violate the rules in school because of their interest in learning. Students who are often in trouble, for example, students who do not have time to start learning, do not use the attributes of the school, skip the time the learning is going on, does not obey the school order. The research method uses this method because in the design of the exsperimental design method, the non-equivalent control group design pattern contains control groups and experimental groups. The sample was 12 students who were divided into two groups, an experimental group and a control group. The research population of all high school students Hidayaun Najah 32 students and by calculating the results using the output analysis test SPSS version 22.0 for windows. The study was conducted using the treatment technique behavior contract that was performed as many as 8 meetings with a duration of 30-40 minutes based on the results of the test sig. ( 2-tailed) is 0,000 < 0.05. After conducting the disciplinary treatment the students gave the experimental group 67.6% including the category quite effective while the control group 36.2% included the category less effective thus Ho was rejected and Ha received the voiced "Guidance Group Technical Behaviour Contract Really Effective in Improving High School Discipline Hidayatun Najah". Keywords : Contractual behavior technique group guidance, student discipline